2016
DOI: 10.1007/s40520-016-0668-5
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Japanese version of the SARC-F for diabetic patients: an examination of reliability and validity

Abstract: The retest reliability of SARC-F-J was regarded to be good. When EWGSOP was assumed as a reference, the specificity of SARC-F-J was high. Because the sensitivity was low, patients with sarcopenia could not be screened, and hence, attention is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 31 publications
3
75
3
1
Order By: Relevance
“…In other Asian population studies, Kim et al . and Ida et al . reported that detection of sarcopenia defined by certain criteria, such as the EWGSOP and AWGS, showed similar specificity and sensitivity to Woo et al .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In other Asian population studies, Kim et al . and Ida et al . reported that detection of sarcopenia defined by certain criteria, such as the EWGSOP and AWGS, showed similar specificity and sensitivity to Woo et al .…”
Section: Discussionmentioning
confidence: 77%
“…Several researchers have examined the SARC‐F's utility in detecting current sarcopenia . Woo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that sensitivity and specificity of SARC‐F in Chinese elderly patients residing in communities were 4.2% and 98.7% for men and 9.9% and 94.4% for women, respectively. In our previous study involving elderly patients with diabetes, the sensitivity of SARC‐F was 14.6% for men and 33.3% for women, and the specificity was 85.8% for men and 72.4% for women. Despite slight differences, these trends in sensitivity and specificity were similar to those observed in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…SARC‐F is a self‐administered questionnaire assessing five items: strength, assistance in walking, rising from a chair, climbing stairs, and falls. Recently, we created the Japanese version of SARC‐F questionnaire (SARC‐F‐J) for elderly patients with diabetes . The sensitivity of this screening tool was 14.6% and 33.3% for men and women, respectively, and the specificity was 85.8% and 72.4%, respectively, using the definition of sarcopenia established by EWGSOP as reference.…”
Section: Introductionmentioning
confidence: 99%